Accuracy and reproducibility of a newly developed tool for volume measurements of the arm using 3D stereophotogrammetry. Issue 12 (December 2017) - Verhulst, A.C.; Wesselius, T.S.; Glas, H.H.; Vreeken, R.D.; Ulrich, D.J.O.; Maal, T.J.J.
Summary: Background: Lymph edema of the arm is a common complication after breast cancer treatment. To evaluate lymph edema volume and treatment outcome, an easy to use, objective quantification method of arm volume is necessary. Most often, water displacement is used to measure arm volume, as it is an easy and robust method that can be performed at any place with a simple equipment. However, when using water displacement, no exact localization of volume difference can be seen. To accurately measure hand and forearm volumes separately, an in-house-developed device was constructed for an accurate landmark placement. Method: An in-house developed measurement tool was used for placing artificial landmarks proximal to the wrist crease on ten healthy subjects. Three-dimensional (3D) images of the hand and forearm were acquired, and volume measurements of the hand and forearm were performed. Measurements were repeated to investigate the intra- and inter-rater variability caused by the landmark placement. Results: Measuring volume of the hand and forearm while using artificially placed landmarks turned out to be a highly reproducible, quick, and easy procedure. Both intra- and inter-rater variability showed high reproducibility for hand (ICC = 0.96 and 0.98, respectively) and forearm (ICC = 0.99 and 0.99, respectively) volumes. Conclusion: Measuring volumes of the hand and forearm while using artificially placed landmarks was found to be a highly reproducible, quick, and easy procedure. The device enables to analyze the localization of lymph edema in greater details.